P210 Peri-operative treatment of sleep-disordered breathing and outcomes in bariatric patients. (15th November 2017) - Meurgey, JH; Brown, R; Woloszyl, A; Steier, J
Abstract : Background: Obstructive sleep apnoea (OSA) is common in bariatric patients undergoing sedation during surgery. However, its contribution to peri-operative respiratory complications and mortality has not been established. We sought to pre-operatively identify OSA in bariatric patients and record peri-operative complications following bariatric surgery. Methods: Data were collected and analysed from June 2014 to March 2017 for 410 bariatric surgery patients referred to the sleep laboratory for pre-operative screening and treatment of OSA. The STOP-BANG questionnaire, Epworth Sleepiness Scale (ESS) and nocturnal pulse oximetry were recorded and treatment was allocated with continuous positive airway pressure (CPAP). Peri-operative complications and mortality were the primary outcome measures for patients receiving CPAP treatment for OSA, with patients not requiring CPAP used as control. The mean follow-up time for all patients was 433 days; 732 days for the patients who had undergone bariatric surgery. The two groups were compared with Chi- square test and unpaired two-tailed t-test. Results: Significant OSA was present in 70% of the screened patients, 40% of patients involved in the study received CPAP treatment. Patients receiving CPAP treatment [49.5 (11.3) years old, 61% female, 50.3 (8.5) kg/m2] were older, had a lower female percentage and had a higher BMI than those not receiving CPAP [44.9 (12.0), 81% female, 46.6 (7.7)]. No significant differences, including hospital stay or rate of complications, were observed between patients on CPAP and those not on CPAP. Out of 53 patients who had undergone bariatric surgery at the cut-off date, only 1 respiratory complication had occured. Conclusion: Bariatric patients who are screened pre-operatively for OSA and treated per guidelines have no increased risk of respiratory complications compared to patients without OSA.